Dielectric spectroscopy in biodiesel production and characterization - Romano, Silvia Daniela (Green energy and technology, 2011)
Dielectric Spectroscopy in Biodiesel Production and Characterization presents the application of dielectric techniques in the production process of biodiesel, and in the characterization of biofuels, raw materials and effluents. In this comprehensive text, the reader will find information about biodiesel, production processes and biofuel characterization, including a description of dielectric techniques that are a useful alternative to ? and have some important advantages over ? the methods indicated in international standards. Dielectric Spectroscopy in Biodiesel Production and Characterization is written in a language that is easy for both specialists and non-specialists to understand. It provides the concepts and tools needed for the application and correlation of the results of dielectric measurement with those from other techniques that are included in international standards. Aimed at a broad audience, the book gives a unified presentation, in a clear and concise way, of up-to-date information that has been gathered from a wide range of sources. Based on the ample research and teaching experience of the authors, Dielectric Spectroscopy in Biodiesel Production and Characterization will be of interest to professionals working in the liquid biofuels industry, researchers entering the field and also advanced university students on related courses.